Characterization of Bacillus spp. from the rhizosphere of potato Granola varieties as an antibacterial against Ralstonia solanacearum - Nur Prihatiningsih; Triwidodo Arwiyanto; Bambang Hadisutrisno; Jaka Widada (Society for Indonesian Biodiversity, 2020)
Abstract. Prihatiningsih N, Arwiyanto T, Hadisutrisno B, Widada J. 2020. Characterization of Bacillus spp. from the rhizosphere of potato Granola varieties as an antibacterial against Ralstonia solanacearum. Biodiversitas 21: 4199-4204. Ralstonia solanacearum is one of the important wilt pathogens that significantly decreased potato yields in Indonesia. One of the strategies to control wilt disease is the use of Bacillus sp. that isolated from potato rhizosphere. Bacillus sp. is an antagonist against some phytopathogenic fungi and bacteria.   The objectives of the study were to identify 5 strains of Bacillus spp. (B46, B209, B211, B298, and B315) that is capable of suppressing the growth of R. solanacearum. Experimental assays were performed to determine the growth inhibition of R. solanacearum by culturing in a two-layer medium. The identification of Bacillus spp. was performed based on physiological and biochemical characters and molecular identification. Results showed that all of Bacillus spp. are capable of suppressing the growth of R. solanacearum. B. subtilis B315 isolate was the most effective biocontrol agent in inhibiting R. solanacearum growth by a bacteriostatic mechanism.  All Bacillus spp.  have similarities in physiological and biochemical characters. Based on the molecular analysis, Bacillus sp. B46, B209, B211, and B298 were homologous to B. subtilis subspecies spizizeni RRLKE2, whereas Bacillus sp. B315 was homologous to B. subtilis strain WIFD5.